Change in socioeconomic educational equity after 20 years of PISA: A systematic literature review - Ekaterina Enchikova; Tiago Neves; Cibelle Toledo; Gil Nata (International Journal of Educational Research Open)
Since its beginning in 2000, the OECD's Program for International Student Assessment (PISA) declared the promotion of educational equity as one of its core values and goals. For more than 2 decades, OECD and independent researchers have been taking advantage of the PISA datasets, using them to measure, explore and monitor the changes in educational equity, which has resulted in a comprehensive body of literature. This review offers a summary of official reports and independent studies regarding the change in socioeconomic equity in different countries based on PISA data analysis. We explore four types of educational equity (Equality of Opportunity, Equality of Outcome, Segregation, and Resilience) and summarize the results of the reviewed studies based on their method, geography, and reported trend of change.